2018
DOI: 10.1021/acsinfecdis.8b00161
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of nTZDpa as an Antibiotic Effective Against Bacterial Persisters

Abstract: Conventional antibiotics are not effective in treating infections caused by drug-resistant or persistent nongrowing bacteria, creating a dire need for the development of new antibiotics. We report that the small molecule nTZDpa, previously characterized as a nonthiazolidinedione peroxisome proliferator-activated receptor gamma partial agonist, kills both growing and persistent Staphylococcus aureus cells by lipid bilayer disruption. S. aureus exhibited no detectable development of resistance to nTZDpa, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 15 publications
4
46
1
Order By: Relevance
“…We reported a similar result in a previous SAR study on nTZDpa (12), where we observed that nTZDpa-analogs 6 and 11 ( Fig. 4 B and C) induced rapid SYTOX Green permeabilization, but did not affect the viability of MRSA persisters (12).…”
Section: The Killing Of Mrsa Persisters Is Correlated With Increased supporting
confidence: 89%
See 3 more Smart Citations
“…We reported a similar result in a previous SAR study on nTZDpa (12), where we observed that nTZDpa-analogs 6 and 11 ( Fig. 4 B and C) induced rapid SYTOX Green permeabilization, but did not affect the viability of MRSA persisters (12).…”
Section: The Killing Of Mrsa Persisters Is Correlated With Increased supporting
confidence: 89%
“…Indeed, transmission electron micrographs (TEMs) showed that 10× MIC bithionol disrupts MRSA membranes, causing the intracellular formation of mesosome-like structures, abnormal cell divisions, and cell lysis (Fig. 1B), which we previously observed when S. aureus cells were treated with membrane-active antimicrobials (12).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…We identified several bioactive compounds, of which biological activities have been previously determined [ 20 ]. For example, the selective retinoic acid receptor γ (RARγ) agonist CD437 and CD1530 [ 19 ], the selective peroxisome proliferator-activated receptor γ (PPARγ)-agonist nTZDpa [ 21 ], the anti-parasite drug bithionol [ 22 ], and insulin-like growth factor receptor inhibitor PQ401 [ 23 ]. Each show promising antimicrobial potency against multidrug-resistant Gram-positive pathogens and their persister cells.…”
Section: Introductionmentioning
confidence: 99%